(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
Currently, universities face the challenge of transitioning senior classes to specialized education. This problem is complex and requires extensive research. It is currently being widely discussed among educators, psychologists, and methodologists. In the concept of specialized education at the senior level of comprehensive school, the proposed profiles are merely outlined but not developed, and specialized education in the proposed form has not been researched. The issue of preparing future teachers for work in a specialized education environment remains unresolved. However, the success of the transition to specialized education largely depends on this. Groups with various focus areas have already been established, with pedagogical groups occupying a special place among them. The pedagogical profile guides senior students toward the teaching profession, which is widely practiced. Furthermore, the pedagogical profile facilitates the concept of continuous teacher training in the "specialized class - pedagogical university - specialized class" system, which has a cyclical nature.